Systematic Literature Review: Implementation of Government Accounting Standards (GAS) and Their Impact on Regional Financial Accountability - Jannah, Miftahul; Haliah, Haliah; Nirwana, Nirwana (DINASTI RESEARCH, 2025)
This research is a systematic literature review aimed at evaluating the implementation of Government Accounting Standards (GAS) and their impact on regional financial accountability. Through a Systematic Literature Review (SLR) approach, various previous studies are analyzed to identify patterns, challenges, and the contributions of GAS in improving transparency and responsibility in public financial management at the regional government level. The study finds that the implementation of GAS generally leads to improvements in the presentation of regional financial statements, particularly in terms of comparability, relevance, and reliability of information. However, the review also reveals several obstacles, stemming from technical aspects, human resources, and suboptimal institutional commitment. In addition, consistent implementation of GAS has been shown to correlate with enhanced internal and external oversight, which in turn supports the achievement of better accountability. This study emphasizes the importance of alignment between regulations, training, and technological utilization in strengthening the role of GAS. By summarizing key findings from various studies, this review provides valuable insights for policymakers and other stakeholders in improving public sector accounting practices in Indonesia.